Report Card on Physical Activity for Children and Youth - Mota, J (2016)
Background: This article describes the procedures and development of the rst Portuguese Report Card on Physical Activity in Children and Adolescents. Methods: Comprehensive searches for data related to indicators of physical activity (PA) were completed by a committee of physical activity and sports specialists. Grades were assigned to each indicator consistent with the process and methodology outlined by the Active Healthy Kids Canada Report Card model. Results: Nine indicators of PA were graded. The following grades were assigned: Overall Physical Activity Levels, D; Organized Sport Participation, B; Active Play, D; Active Transportation, C; Sedentary Behaviors, D; Family and Peers, C; Schools, B; Community and the Built Environment, D; and Government, C. Conclusions: Portuguese children and adolescents do not reach suf cient physical activity levels and spend larger amounts of time spent in sedentary behaviors compared with recommendations. Effective policies of PA promotion and implementation are needed in different domains of young people’s daily lives.